Construction of Public Culture from the Perspective of Public Management - Hamamoto NARISA (International Journal of Social Sciences and Public Administration, 2024)
The construction of public culture is one of the components of the public management system. The purpose of public culture construction is to realize the equal ownership of cultural rights, so it is a natural selection to combine it with public management. The article will elaborate on three aspects: the focus of integrating with public management, the current problems in public cultural construction, and how to optimize cultural construction.